Sepsis-induced regulation of lipoprotein lipase expression in rat adipose tissue and soleus muscle - S Lanza-Jacoby; N Sedkova; H Phetteplace; D Perrotti (Journal of Lipid Research, 1997)
Hypertriglyceridemia of sepsis is associated with suppressed tissue lipoprotein lipase (LPL) activities. We investigated the effect of sepsis on lipoprotein lipase gene expression in epididymal fat and soleus muscle from control and septic rats in the fasted and fed state. After 24 h of sepsis, LPL activity decreased significantly in epididymal fat from fasted rats by 45% along with a 57% reduction in LPL mRNA levels and LPL mass. Transcription rate, measured by nuclear run-on assay, decreased by 70% in epididymal fat from fasted septic rats compared to fasted control rats. The synthesis rate of LPL in epididymal fat decreased by 31% while the LPL relative synthesis declined by 50% during sepsis. The turnover rate was not altered. Sepsis in fed rats did not lead to a significant decrease in LPL mRNA in epididymal fat but did lower LPL activity and LPL mass by 45%. The sepsis-induced suppression in soleus LPL activity, LPL mRNA levels, and LPL mass in the fasted state also was observed when septic rats were fed. The results indicate that during fasting sepsis, LPL expression in epididymal fat and possibly soleus muscle involves transcriptional regulation. During sepsis in the fed state, the regulation of LPL in adipose tissue may involve posttranslational mechanisms.